2021
DOI: 10.1002/rmv.2308
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor erythroid 2‐related factor 2 in human papillomavirus‐related cancers

Abstract: High-risk human papillomavirus (HR-HPV) infection is a necessary cause for the development of cervical cancer. Moreover, HR-HPV is also associated with cancers in the anus, vagina, vulva, penis and oropharynx. HR-HPVs target and modify the function of different cell biomolecules, such as glucose, amino acids, lipids and transcription factors (TF), such as p53, nuclear factor erythroid 2-related factor 2 (Nrf2), among others. The latter is a master TF that maintains redox homeostasis.Nrf2 also induces the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 133 publications
0
6
0
Order By: Relevance
“…Previous studies have shown frequent activating mutations of the KEAP1-NRF2 pathway in HNSC along with increased enrichment of its signatures. Other studies have shown suggested alternative mechanisms for activated NRF2 signaling such as upregulation of the c-MYC pathway or by HPV [ 39 , 40 ]. To date, no report has linked mutations in SWI/SNF subunits, such as ARID1A, to activation of NRF2 signaling in HNSC.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown frequent activating mutations of the KEAP1-NRF2 pathway in HNSC along with increased enrichment of its signatures. Other studies have shown suggested alternative mechanisms for activated NRF2 signaling such as upregulation of the c-MYC pathway or by HPV [ 39 , 40 ]. To date, no report has linked mutations in SWI/SNF subunits, such as ARID1A, to activation of NRF2 signaling in HNSC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the kinases involved in this pathway also directly phosphorylates transcription factor NRF2 (the product of Nfe2l2 ) in response to environmental stress 91 and NRF2 was predicted to be activated in MnPV‐induced tumors in both datasets (Figures 3C and 5F). Its activation increases the expression of cytoprotective proteins, 44,93 thereby preventing DNA damage and virus integration into the host genome, while its deactivation could cause genome instability 94 . So far, cutaneous PVs are not known to integrate into the host genome and since NRF2 also inhibits the NLRP3 inflammasome, 95 its activation may be a strategy to maintain viral episomes.…”
Section: Discussionmentioning
confidence: 99%
“…Its activation increases the expression of cytoprotective proteins, 44,93 thereby preventing DNA damage and virus integration into the host genome, while its deactivation could cause genome instability. 94 So far, cutaneous PVs are not known to integrate into the host genome and since NRF2 also inhibits the NLRP3 inflammasome, 95 its activation may be a strategy to maintain viral episomes.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the fourth most frequently diagnosed malignant disease among women worldwide, with 604,000 new cases in 2020 [39], mainly caused by human papillomavirus (HPV) infection [40]. The integration of the viral genome with the human host is essential for cancer progress, and oxidative stress plays an important role in viral integration and persistent virus infection [41].…”
Section: Cervical Cancermentioning
confidence: 99%